O12.7. TREATMENT WITH CANNABIDIOL REDUCES RESTING STATE PERFUSION IN INDIVIDUALS AT CLINICAL HIGH RISK FOR PSYCHOSIS. (9th April 2019) - Bossong, Matthijs; Wilson, Robin; Appiah-Kusi, Elizabeth; Linsen, Felix; Zelaya, Fernando; Allen, Paul; McGuire, Philip; Bhattacharyya, Sagnik
Abstract: Background: The non-intoxicating cannabinoid compound cannabidiol (CBD) may have the potential to become a new effective, safe and well-tolerated antipsychotic drug. CBD may be particularly feasible as a treatment for people at clinical high risk (CHR) for the development of psychosis due to its lack of serious side effects. Preclinical models suggest that abnormalities in functioning of the medial temporal lobe and striatum are fundamental in the pathophysiology of psychosis. Recent neuroimaging studies showed increased resting state perfusion in these brain regions in CHR individuals, but it is unknown how this is affected by CBD treatment. Here we examined the impact of treatment with CBD on resting state perfusion in people at CHR for psychosis. Methods: Using a parallel-group, double-blind, placebo-controlled, randomised design, 33 individuals who met CHR criteria were treated for three weeks with either a single daily oral dose of 600 mg CBD (N=16) or placebo (N=17). Resting state perfusion was measured three hours after the first administration (day 1) and after three weeks of treatment (day 21) using Arterial Spin Labelling (ASL). Complete ASL data sets were obtained for 23 CHR individuals (placebo N=10, CBD N=13). ASL images were preprocessed in SPM8 and normalised for global perfusion. Resting state perfusion was examined in a network relevant to psychosis comprising the parahippocampal gyrus, hippocampus and striatum. Mean perfusion values were extracted from these brain areas and analysed in SPSS. Symptomatology was assessed with the Comprehensive Assessment of At-Risk Mental State (CAARMS) at baseline and after three weeks of treatment. For both symptomatology and perfusion, difference scores were calculated by subtracting results from the first measurement from those obtained at the follow-up assessment. Group and treatment effects were determined with two-sample t-tests or χ2 tests and associations with Pearson's correlation. Results: There were no significant differences between the two treatment groups in terms of age, gender, years of education, handedness or baseline symptomatology. Treatment with CBD significantly reduced resting state perfusion in the psychosis network compared to placebo (-0.009±0.034 and 0.028±0.042, p=0.031). Post hoc analysis revealed a trend towards a significant decrease in perfusion after CBD treatment in the parahippocampal gyrus (-0.015±0.057 and 0.030±0.052, p=0.063). No significant post hoc treatment effects were found on perfusion in the hippocampus (CBD -0.008±0.066, placebo 0.027±0.062, p=0.216) or striatum (CBD -0.006±0.047, placebo 0.026±0.050, p=0.126). Total symptom scores decreased with CBD treatment compared to placebo, although this did not reach significance (-58.6±54.4 and -28.9±62.5, p=0.157). There were no significant correlations between resting state perfusion and symptomatology. Discussion: Three-week treatment with CBD reduced resting state perfusion of individuals at CHR for the development of psychosis in a brain network comprising the medial temporal lobe and striatum. This is consistent with previous neuroimaging work that showed that resolution of the high-risk state was associated with attenuation of resting perfusion in these areas. Our findings suggest that the therapeutic effects of CBD in CHR individuals may be mediated through normalisation of regional resting state perfusion. Results support further examination of CBD as a treatment for people at CHR for psychosis in large-scale multicentre clinical trials.